GmNAC181 promotes symbiotic nodulation and salt tolerance of nodulation by directly regulating GmNINa expression in soybean. Issue 2 (15th July 2022) - Wang, Xiaodi; Chen, Kuan; Zhou, Miaomiao; Gao, Yongkang; Huang, Huimei; Liu, Chao; Fan, Yuanyuan; Fan, Zihui; Wang, Youning; Li, Xia
Summary: Soybean ( Glycine max ) is one of the most important crops world‐wide. Under low nitrogen (N) condition, soybean can form a symbiotic relationship with rhizobia to acquire sufficient N for their growth and production. Nodulation signaling controls soybean symbiosis with rhizobia. The soybean Nodule Inception ( GmNINa ) gene is a central regulator of soybean nodulation. However, the transcriptional regulation of GmNINa remains largely unknown. Nodulation is sensitive to salt stress, but the underlying mechanisms are unclear. Here, we identified an NAC transcription factor designated GmNAC181 (also known as GmNAC11) as the interacting protein of GmNSP1a. GmNAC181 overexpression or knockdown in soybean resulted in increased or decreased numbers of nodules, respectively. Accordingly, the expression of GmNINa was greatly up‑ and downregulated, respectively. Furthermore, we showed that GmNAC181 can directly bind to the GmNINa promoter to activate its gene expression. Intriguingly, GmNAC181 was highly induced by salt stress during nodulation and promoted symbiotic nodulation under salt stress. We identified a new transcriptional activator of GmNINa in the nodulation pathway and revealed a mechanism by which GmNAC181 acts as a network node orchestrating the expression of GmNINa and symbiotic nodulation under salt stress conditions.